Actualización del manejo, diagnóstico y tratamiento de la Laringotraqueitis en pacientes pediátricos. - Olivo Acurio, Angie Jazmín (2023)
ABSTRAC Introduction: Upper respiratory tract infections represent the most common pathologies evaluated in the outpatient setting, and range from the common cold to life-threatening diseases such as epiglottitis. Croup, also known as Laryngotracheitis, is part of these conditions and is characterized by inspiratory stridor, barking cough and dysphonia. Its symptoms result from an upper respiratory tract infection that causes inflammation of the larynx, trachea and bronchi. Its causes can be both viral and bacterial, parainfluenza virus is the most common with around 70% of cases, on the other hand, Mycoplasma Pneumoniae can cause a primary bacterial infection that leads to Laryngotracheitis. Objective: Conduct a bibliographic review to update the management, diagnosis and treatment of Laryngotracheitis in pediatric patients in order to reduce hospital emergencies. The aim is to delve deeper into the correct diagnosis based on establishing clinical characteristics, differential diagnoses, treatment updates and complications. Methodology: This research is qualitative, descriptive, retrospective with a non-experimental design, it is mainly supported by the synthetic method and the qualitative, descriptive approach that aims to analyze sources such as indexed journals of aspects and components consistent with the research. Results and discussion: Multiple scientific articles have been analyzed from which an optimal treatment for this condition has been identified. Glucocorticoids are generally selected due to their high effectiveness compared to other alternatives, their use as regular therapy helps reduce edema in the airways, they produce an improvement within 6 hours after their administration and are linked to less use of co-interventions and Shorter hospital stay. KEYWORDS: Croup, Laryngotracheitis, Westley Scale, Glucocorticoids